Brand Guardian in a ‘Fragile’ Society - Dyah Hasto Palupi; Dwi Wulandari; Nurur Bintari; Wawan Setiawan (Jobmark: Journal of Branding and Marketing Communication, 2019)
Although the duties and responsibilities of brand guardianship are on a collective scale, their success depends on the hard work of each brand guardian according to their roles and capacities. In the era of disruption, the challenges are even more significant and more diverse.